Evaluasi Akreditasi di Perpustakaan Candakarana SMA Negeri 2 Kebumen - Ahmad Ahmad; Muna Fauziah; Bahrun Ali Murtopo (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2020)
This study intends to analyze the evaluation of accreditation at the Candakarana library of SMA Negeri 2 Kebumen. This study uses qualitative research which takes place in the Candakarana library of SMAN 2 Kebumen. Data were collected by observation, interview and documentation methods. Data validity was carried out using the triangulation technique, while data analysis used the selection and arrangement of the data obtained. Then, the data is processed and analyzed to make conclusions. The results of the research are that the evaluation system is carried out through controlling the progress of accreditation every weekend through two stages (pre-accreditation by checking the readiness of accreditation documents and post-accreditation by giving rewards to the accreditation team), as well as internal and external school obstacles.